Band edge tuned ZnxCd1−xS solid solution nanopowders for efficient solar photocatalysis. Issue 44 (2nd November 2017) - Ghosh, Shrabani; Sarkar, Samrat; Das, Bikram Kumar; Sen, Dipayan; Samanta, Madhupriya; Chattopadhyay, Kalyan Kumar
Abstract : Natural sunlight assisted catalytic activity of hydrothermally synthesized zinc blende Zn x Cd1− x S solid solution with theoretical insights. Abstract : This work highlights the synthesis of zinc blende Zn x Cd1− x S ternary solid solutions with a tunable bandgap. Composition dependent band gaps are realized due to the effective band edge tuning of the solid solutions which in turn show decent photocatalytic behaviour. The bandgap of Zn x Cd1− x S increases as Zn composition increases. It is interesting to note that the highest catalytic activity is observed for Zn0.8 Cd0.2 S ( E g = 2.83 eV) in the visible spectra due to the presence of defect states in the bandgap around 2.35 eV which has been explicated according to the results of photoluminescence spectra. Density of states (DOS) analysis provides further theoretical insight into the more negative conduction band edge for x = 0.8 than other samples. It also determines generation of intermediate states due to sulfur vacancy which is responsible for more electron–hole generation and the highest rate of Methyl Orange (MO) degradation under natural sunlight irradiation.